Diet and health in a time of transition: Pictish and Viking Age Orkney - Johnson, AC (2021)
There have long been conflicting interpretations of the archaeological and written evidence for the nature of interactions between the Orcadian Pictish populations and Scandinavian migrants during the Viking Age, with theories ranging from peaceful intermarriage to violent domination of the Picts (Bäcklund 2001; Leonard 2011; Smith 2001; etc.). However, changes in diet and health from the Pre-Viking phase (PVP, 500-790) through the Viking Age (VA, 790-1050) and Late Norse phase (LNP, 1050-1200) suggest more nuanced changes, reflecting evolving subsistence practices and differences in social constructs of ethnicity, religion and status.